Comparing student performance on paper- and computer-based math curriculum-based measures. - Hensley, Kiersten; Rankin, Angelica; Hosp, John (Assistive Technology)
As the number of computerized curriculum-based measurement (CBM) tools increases, it is necessary to examine whether or not student performance can generalize across a variety of test administration modes (i.e., paper or computer). The purpose of this study is to compare math fact fluency on paper versus computer for 197 upper elementary students. Students completed identical sets of probes on paper and on the computer, which were then scored for digits correct, problems correct, and accuracy. Results showed a significant difference in performance between the two sets of probes, with higher fluency rates on the paper probes. Because decisions about levels of student support and interventions often rely on measures such as these, more research in this area is needed to examine the potential differences in student performance between paper-based and computer-based CBMs.